Heart Ablation Sing a Planar Rectangular High Intensity Ultrasound Transducer and MRI Guidance - Birer, Alain; Chapelon, Jean Yves; Kyriacou, Panayiotis A.; Damianou, Christakis A.; Couppis, Andreas; Lafon, Cyril; Chavrier, Francoise (My University, 2012)
The aim of this study was to evaluate a flat rectangular (3 × 10 mm2) MRI compatible transducer operating at 5 MHz. The main task was to explore the feasibility of creating deep lesions in heart at a depth of at least 15 mm. The size of thermal necrosis in heart tissue was estimated as a function of power and time using a simulation model. The system was then tested in an excised lamb heart. In this study, we were able to create lesions of 15 mm deep with acoustic power of 6 W for an exposure of approximately 1 min. The contrast to noise ratio (CNR) between lesion and heart tissue was evaluated using fast spin echo (FSE). The CNR value was approximately 22 using T1 W FSE. Maximum CNR was achieved with repetition time (TR) between 300 and 800 ms. Using T2W FSE, the corresponding CNR was approximately 13 for the 14 in vivo experiments. The average lesion depth was 11.93 mm with a standard deviation of 0.62 mm. In vivo irradiation conditions were 6 W for 60 s. The size of the lesion in the other two dimensions was close to 3 × 10 mm2 (size of the transducer element).
Keywords: Hyperthermia; Medical ultrasonics; Ultrasound in surgery; Therapeutics